DAMPAK KEBIJAKAN SISTEM BELAJAR DARING DI SMP NEGERI 3 LIMBOTO KABUPATEN GORONTALO - Gintulangi, Sri Lestari; Domili, Zulham (STISIPOL Mujahidin Buol, 2022)
This research was conducted at SMP Negeri 3 Limboto with the aim of knowing the Impact of the Online Learning System Policy at SMP Negeri 3 Limboto. The method used is a qualitative method with a descriptive type. Data collection techniques used observation sheets or direct interviews with informants. The results of this study indicate that there are impacts arising from the implementation of the Online Learning System Policy at Limboto 3 Public Middle School, namely student acceptance of ineffective learning materials, no emotional bonds between students and teachers, and can be the cause of the growth of a lazy attitude in oneself. student. The conclusion from this study is that there is a positive impact, namely that students can be avoided from the spread of the corona virus, can improve the soul of teachers and parents and can save time and money as well as a negative impact so that student acceptance of learning materials is not effective, bonds are not established. emotional relationship between students and teachers, and can be the cause of the growth of lazy attitudes in students.